Pemanfaatan Limbah Plastik Menjadi Paving Block Sebagai Upaya Pemberdayaan Masyarakat Dalam Pengolahan Sampah - Makarim, M. Nabil; Pembayun, Aditya Sekar; Rahmadhani, Laili Novita; Marsenda, Euis; Athifah, Jenny Najwa; Ramadhanu, Tio Tri; Purwanto, Lutfi Aldiansyah; Saputro, Kaka Hendro Riyan; Zayyan, Rakha Alzena; Sugiarto, Muhammad Ezar; Wijaya, Titis Wisnu (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Plastic waste is one type of waste that is difficult to decompose and is a serious environmental problem. In Sumberejo Village, Batur District, Banjarnegara, the problem of plastic waste is still difficult to overcome, even in the conservation area there are piles of garbage. Household waste production is the main cause of the accumulation of waste, people who do not understand and are lazy to sort waste are the main reasons for the piles of plastic waste. One solution to reduce the negative impact of plastic waste is to process it into useful building materials, one of which is paving blocks. This community service aims to study the potential for utilizing plastic waste as a basic material for paving blocks, with the hope of reducing the amount of plastic waste that pollutes the environment while providing an alternative environmentally friendly material in the construction world. The methods used in this community service include collecting plastic waste, cleaning, and shredding plastic into smaller forms. The processed plastic is then mixed with aggregate and cement in a certain composition to produce paving blocks. Tests are carried out to determine the compressive strength, durability, and physical stability of the resulting paving blocks. The results of the community service show that paving blocks made from plastic waste have quite good compressive strength and meet the standards set for paving block materials. In addition, the use of plastic waste in making paving blocks provides dual benefits, namely reducing plastic pollution in the environment and providing cheaper and more environmentally friendly construction materials. Therefore, the use of plastic waste as a paving block material can be an innovative solution in overcoming the problem of plastic waste while supporting more sustainable development in Sumberejo Village. Community acceptance of plastic-based paving blocks has proven positive, especially after trials in the local environment. This community service contributes to better plastic waste management and offers new economic opportunities in the construction sector, while supporting sustainable development in Sumberejo Village, Batur District, Banjarnegara Regency, Central Java.